Effect of row spacing and sowing direction on performance of wheat in Kandahar region of Afghanistan - Faiz, Mukhtar Ahmad; Dhar, Shiva; Baray, Shah Mahmood; Dass, Anchal; Khalili, Azizullah (Annals of Agricultural Research, 2016)
A field experiment was carried out at Tarnak Farm of Afghanistan National Agricultural Science and Technology University (ANASTU) Kandahar, Afghanistan during winter season of 2014-2015 to study the effect of row spacing and sowing direction on growth and yield of wheat varieties. The experiment was laid out in FRBD and replicated thrice consisted of two varieties (Shisham Bagh and PBW 154), three row spacing (15, 20 and 25 cm) and two sowing directions (East-West and North-South). Result revealed that more effective tillers m–2 (402.3) and grains spike–1 were obtained from PBW 154 planted at 20 cm row spacing in East-West direction. Significantly higher 1000-grain weight (45.4 g) produced by PBW 154 sown at 20 cm row spacing in N-S direction. Higher grain yield (6.4 t ha–1) and harvest index (47.5%) were recorded from PBW 154 sown at 20 cm row spacing in E-W direction but straw and biological yields were higher in Shisham Bagh sown at 20 cm row spacing in North-South direction.